Role of melatonin in attenuation of haemodynamic responses to laryngoscopy and intubation - Gupta, Priyamvada (Indian J Anaesth, 2016)
BACKGROUND AND AIMS: Laryngoscopy and endotracheal intubation are considered as potent stimuli which lead to an increase in heart rate and blood pressure. Melatonin (N-acetyl-5-methoxytryptamine) has been studied for pre-operative anxiolysis and sedation in Intensive Care Unit. We made a hypothesis that melatonin can provide haemodynamic stability during laryngoscopy and intubation when given 120 min before the procedure. METHODS: Sixty American Society of Anesthesiologists physical status Grade I and II patients of either gender, 20–45 years old, 40–65 kg body weight, scheduled to undergo elective surgical procedures under general anaesthesia were assigned into two equal groups - Group C (control) and Group M (melatonin). They received oral placebo or melatonin tablets 6 mg, respectively, 120 min before surgery. The haemodynamic parameters were recorded preoperatively, during laryngoscopy and endotracheal intubation and thereafter at 1, 3, 5 and 10 min. Unpaired t-test was used for between-group comparison of ratio and interval scale data. For within-group comparison of ratio and interval scale data, repeated-measures ANOVA and post hoc Bonferroni t-tests were used. RESULTS: It was observed that in the control group, there was a significant increase in heart rate and blood pressure at laryngoscopy and intubation and persisted till 10 min post-intubation. In melatonin group, there was an insignificant increase in heart rate at the time of laryngoscopy and intubation which however settled within 1 min post-intubation. CONCLUSION: Melatonin is an effective drug for attenuation of cardiovascular responses to laryngoscopy and endotracheal intubation.